2020
DOI: 10.1002/iju5.12167
|View full text |Cite
|
Sign up to set email alerts
|

Progressive plasmacytoid variant bladder cancer with retroperitoneal dissemination: An autopsy case report

Abstract: Introduction Plasmacytoid urothelial carcinoma is a rare and aggressive variant of bladder cancer. Case presentation A 75‐year‐old woman presented with plasmacytoid urothelial carcinoma with retroperitoneal dissemination was treated with chemotherapy. After an unsuccessful first‐line chemotherapy with gemcitabine and cisplatin, we assessed circulating tumor cells; one such cell was found to be positive for programmed death‐ligand 1. The patient received second‐line chemotherapy with pembrolizumab. However, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 16 publications
(24 reference statements)
0
12
0
Order By: Relevance
“…However, mucosal induration and a thickened bladder wall without masses unlike UC in situ lesions are also shown, which can lead to diagnostic pitfalls [3]. According to the report, cystoscopy revealed that bladder capacity was extremely decreased, and the whole bladder mucosa was irregular and thick at advanced PUC [9]. Otherwise, no masses were seen even after cystoscopic examination, and PUC was diagnosed after mucosal resection was performed [3].…”
Section: Discussionmentioning
confidence: 99%
“…However, mucosal induration and a thickened bladder wall without masses unlike UC in situ lesions are also shown, which can lead to diagnostic pitfalls [3]. According to the report, cystoscopy revealed that bladder capacity was extremely decreased, and the whole bladder mucosa was irregular and thick at advanced PUC [9]. Otherwise, no masses were seen even after cystoscopic examination, and PUC was diagnosed after mucosal resection was performed [3].…”
Section: Discussionmentioning
confidence: 99%
“…In this case, we continued administration of pembrolizumab even after we confirmed pathological CR. A feature of pembrolizumab is a durable response, and a recent 5‐year follow‐up analysis of phase 3 KEYNOTE‐045 trial revealed a median duration of response of more than 2 years for patients with locally advanced or metastatic UC that progressed during or after platinum‐based chemotherapy 7 . Another possibility was to discontinue pembrolizumab treatment after confirmation of the pCR at cystectomy, but considering the aggressive nature of the disease and the benefit of continued activation of CD8 + T cells, we decided to continue treatment with pembrolizumab.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, some cases have reported responsiveness to typical chemotherapeutic agents 19 . Usually, platinum‐based chemotherapy is given with regimes such as methotrexate, vinblastine, doxorubicin, and cisplatin (MVAC) or gemcitabine and cisplatin (GC) 14,20 …”
Section: Introductionmentioning
confidence: 99%
“…19 Usually, platinum‐based chemotherapy is given with regimes such as methotrexate, vinblastine, doxorubicin, and cisplatin (MVAC) or gemcitabine and cisplatin (GC). 14 , 20 …”
Section: Introductionmentioning
confidence: 99%